TINJAUAN HUKUM ISLĀM TERHADAP TRADISI MARTAHI DALAM PERNIKAHAN SUKU BATAK DI KECAMATAN DOLOK - Irham Dongoran (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2017)
Martahi tradision is one of crucial moments in wedding party in batak ethnic at kecamatan dalok. It is a tradition that do by the element of society who will held a wedding party of their son. The purpose to earn some money or fund that would be used as of wedding need that asked by the bride candidate to groom's candidate.To complete that thing, the groom's candidate family do the martahi tradition by inviting relatives, peers, and the elements of the close society. In the Islāmic law perception, the agreement in giving money to the groom's family candidate when doing martahi was agreement in helping, a moral debt and its not about debt but, it more approximate to Alms sunnah